2009
DOI: 10.1108/07363760910965855
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate segmentation model of senior consumers

Abstract: Purpose -The purpose of this study is to provide a multivariate segmentation model of the older consumer market, utilising variables based on the major dimensions of ageing, and behavioural variables previously shown to be pertinent to older adults in the gerontology and marketing literature. Design/methodology/approach -A self-complete questionnaire was administered to an age-based quota sample of 650 older consumers (aged 50-79) in the UK. Using the age and consumer behaviour variables, cluster analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 54 publications
2
95
1
1
Order By: Relevance
“…This growing apart is also reflected in consumer research in terms of needs, lifestyle and consumption (Moschis, Lee, & Mathur, 1997;Sherman & Schiffman, 1991;Sudbury & Simcock, 2009). Although a number of studies show the elderly consumer segment to be heterogeneous, these segmentations usually present a snapshot of a particular moment and do not follow the development of individuals as they age and when or why they grow apart.…”
Section: Age Instabilitiesmentioning
confidence: 99%
“…This growing apart is also reflected in consumer research in terms of needs, lifestyle and consumption (Moschis, Lee, & Mathur, 1997;Sherman & Schiffman, 1991;Sudbury & Simcock, 2009). Although a number of studies show the elderly consumer segment to be heterogeneous, these segmentations usually present a snapshot of a particular moment and do not follow the development of individuals as they age and when or why they grow apart.…”
Section: Age Instabilitiesmentioning
confidence: 99%
“…A popular belief that early adopters tend to be young led Rogers (2003) to a thorough review of the innovation literature, from where he confirmed, 'early adopters are no different from late adopters in age ' (p. 288). In other words, early adopters come in all ages and there are vast differences between groups of baby boomers, with some demonstrating relatively high levels of willingness to try new brands, while others are far less innovative (Sudbury & Simcock, 2009). Thus, H7: Market mavenism is positively related to willingness to try new brands.…”
Section: New Brand Trialmentioning
confidence: 99%
“…Three segments were described: 'Nutrition concerned', 'Fast & healthy' and 'Traditional couponers'. Later, comprehensive segmentation models, using gerontographics of older Americans, were used by and Sudbury and Simcock (2009). Moschis divided the group of older persons into four segments that differed in level of financial independence, healthiness, isolation, socially withdrawnness, solitariness, activity, and acceptance of being 'old.…”
Section: Introductionmentioning
confidence: 99%
“…Moschis divided the group of older persons into four segments that differed in level of financial independence, healthiness, isolation, socially withdrawnness, solitariness, activity, and acceptance of being 'old. ' Sudbury and Simcock (2009) segmented 650 older persons (age 50-79y) based on variables reflecting the major dimensions of ageing and behavioural variables relevant for older adults. Five segments emerged that differed in, for example, general consumer behaviour and behaviour towards marketing campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation